Active learning pedagogy: Structuring the pre-instruction assignment. (January 2019) - Novak, G
Abstract: Education research is changing the way teachers teach and students learn. In contrast with the lecture-based approach to instruction, centered on the teacher as "performer", teaching and learning activities now place equal emphasis on in-class and out-of-class work. Much of the interaction between at-home activity and classroom experience and is mediated by information technology tools. Students are technology savvy, comfortable in the world of on-line delivery of information and social media interactions. To be an effective player in this world, instructional design has to follow the students. Contrary to the opinion that the introduction of technology into the teaching and learning process will diminish the role of the teacher, we believe that the opposite could be the case. Communication technology can enable all students to be exposed to the best and most charismatic lecturers. Electronically enabled social media forums can give rise to much more individualized interactions between students and instructors and students and students than what was ever possible. In this paper, we focus on some pedagogical approaches that allow the students to prepare themselves for interactive classroom engagement. The techniques we describe are labelled Just-in-Time Teaching and Worked-Examples. These involve carefully crafted assignments that students complete before going to class. The results of these assignments, completed just before class-time and available to the instructor, prepare the both for a more productive in-class experience.